Over-And Understeer Behaviour Evaluation by Modelling Steady-State Cornering - Avramov, Nikola; Simonovski, Petar; Rizov, Tashko (Analele Universităţii "Eftimie Murgu", 2012)
This paper gives an overview of a vehicle cornering in a constant cornering radius, with constant speed. These constant values indicate steady state cornering or not changing its motion character over time. Even if the steering angle δ starting from ‘0’ (straight line driving) is reaching the constant value or the constant cornering radius, the vehicle is not following the desired path or evident is the under-steer or over-steer condition. As presented we can see the vehicle cornering, and it’s offset from the neutral driven vehicle. The vehicle is driving trough corner with greater radius. This means that the vehicle is understeered. Neutral driven vehicle is the desired arc which can be followed by vehicle with neutral steer which means that when accelerating the driver doesn’t have to change the angle of the steering wheel.
Keywords: lateral forces; side slip angle; under-steer; over-steer; cornering stiffness